Validation of the standardised assessment of personality – abbreviated scale in a general population sample - Fok, Marcella Lei‐Yee (Personal Ment Health, 2015)
BACKGROUND: Personality disorder (PD) is associated with important health outcomes in the general population. However, the length of diagnostic interviews poses a significant barrier to obtaining large scale, population‐based data on PD. A brief screen for the identification of people at high risk of PD in the general population could be extremely valuable for both clinicians and researchers. AIM: We set out to validate the Standardised Assessment of Personality – Abbreviated Scale (SAPAS), in a general population sample, using the Structured Clinical Interviews for DSM‐IV Personality Disorders (SCID‐II) as a gold standard. METHOD: One hundred and ten randomly selected, community‐dwelling adults were administered the SAPAS screening interview. The SCID‐II was subsequently administered by a clinical interviewer blind to the initial SAPAS score. Receiver operating characteristic analysis was used to assess the discriminatory performance of the SAPAS, relative to the SCID‐II. RESULTS: Area under the curve for the SAPAS was 0.70 (95% CI = 0.60 to 0.80; p < 0.001), indicating moderate overall discriminatory accuracy. A cut point score of 4 on the SAPAS correctly classified 58% of participants. At this cut point, the sensitivity and specificity were 0.69 and 0.53 respectively. CONCLUSION: The SAPAS operates less efficiently as a screen in general population samples and is probably most usefully applied in clinical populations. © 2015 The Authors Personality and Mental Health published by John Wiley & Sons Ltd